Employee willingness to change towards the implementation of smart contract - Sazali, Mohammad Suzaime (2021)
Smart Contract is one of the latest technology introduced into construction industry which provide potential to substitute the traditional contracting method. With an increasing shift towards the adoption and implementation of this technology into construction projects, it is essential to realize how smart contracts can be used for organizational advantages. However, the implementation of Smart Contract possess challenges particularly among construction employee. Therefore, this paper tends to identify the resistance factors in embracing changes among construction employee as well as to determine the factor that influence the employee willingness to implement construction smart contract in Malaysia. Quantitative methodology has been utilized by distributing 120 questionnaire surveys to individuals that possess construction background within Malaysia. A total of 60 respondent’s feedback able to be collected. Data collected are analysed by using reliability test, descriptive analysis, one way ANOVA analysis as well as correlation analysis. The findings shows that most the respondents are agreed that the factors such as employee behaviour, demographic, psychology, social as well as culture possess impact towards employee resistance towards change. Furthermore, the finding also illustrates that the all of the respondent strongly agreed to the factors that influence employee willingness to change towards the implementation of Smart Contract. The factors that influence the employee willingness to change are leadership, communication and collaboration, self-efficacy, personal valence, investment and finally employee engagement. In supposition, construction organization has realized the factors that influence employee resistance to change as well as the factors that can be practice to implement Smart Contract.